Banking concentration, information sharing and women's political empowerment in developing countries - Simplice Asongu; Emeride F. Kayo; Vanessa Tchamyou; Therese E. Zogo (African Governance and Development Institute (AGDI), 2024)
Purpose - This article analyses the effect of bank concentration on women's political empowerment in 80 developing countries over the period 2004-2020. Design/methodology/approach - Banking concentration (BC) is measured by the assets held by the three largest commercial banks as a percentage of total commercial bank assets in a country. We use several indices to measure political empowerment, namely: the political empowerment index, composed of three indices (i.e., the women's civil liberties index, the women's participation in civil society index and the women's political participation index). The empirical evidence is based on the Ordinary Least Squares (OLS) and Fixed Effects (FE) techniques. Findings - The following findings are established. Banking concentration reduces women's political empowerment. Furthermore, information sharing offices (i.e. public credit registries and private credit bureaus) mitigate the negative effect of bank concentration on women's political empowerment. Information sharing thresholds that are needed to completely dampen the negative effect of bank concentration on women's political empowerment are provided. Policy implications are discussed, notably: (i) that governments in developing countries increase competition by easing barriers to entry for potential banks, to facilitate the transition from confiscatory concentration to distributive concentration favorable to all stakeholders; and (ii) information sharing offices should be consolidated beyond the established thresholds in order to completely crowd-out the unfavorable effect of bank concentration of women's political empowerment. Originality/value - The paper provides new empirical evidence that helps to advance the debate on the effects of banking concentration and information sharing in the banking sector on women's political empowerment in developing countries.
Keywords: 330; Banking concentration; women political empowerment; OLS; Fixed Effects